The Moods and Tenses in Eustathian and Late Twelfth-Century High-Style Byzantine Greek - STONE, Andrew Francis (Byzantina Symmeikta, 2010)
This paper investigates certain features of High Byzantine Greek as found in the speeches of Eustathios of Thessaloniki and his contemporaries. It endeavours to show these features are not necessarily hyper-correct forms, but that these authors had a full command of the constructions of the Classical Greek language, and built on these to create their own style.